Enhanced αα-particle production from fusion evaporation reactions leading to 46Ti. (22nd March 2021) - Cicerchia, M; Gramegna, F; Fabris, D; Cinausero, M; Marchi, T; Andreetta, G; Barlini, S; Bini, M; Bolzonella, R; Bruno, M; Buccola, A; Caciolli, A; et al.
Abstract: In this paper, we report a detailed study on the de-excitation of the 46 Ti compound nucleus populated by means of four different reactions: 16 O + 30 Si at 7 and 8 AMeV, 18 O + 28 Si at 7 AMeV and 19 F + 27 Al at 7 AMeV. The GARFIELD detection array was used to measure the light charged particles and the heavy fragments emitted. This setup covers a large fraction of the solid angle with high-granularity. Complete events are chosen through total charge ( Z TOT = 22) detection. Fusion-evaporation events are selected based on the condition that only one heavy fragment is detected in coincidence with the light charged particles. The analysis of global observables, such as charge distribution and light charged particle multiplicities, is compatible with the formation of a thermalized compound nucleus for all the four reactions. Nevertheless, an enhanced emission of α -particles with respect to a pure statistical picture is observed at very forward angles (<20°). This enhancement is mainly visible in the even-Z residue exit channels populated through the emission of only α -particles.